ANALISIS FAKTOR PENYEBAB KRISIS AKHLAK PADA ANAK PESISIR - Isnaini Isnaini (Jurnal Anifa: Studi Gender dan Anak, 2021)
The pronunciation of inappropriate words to exemplify, thus rendering the child devoid of good manners and word-tours, and often against parenthood, is because her parents are unspoiled when she speaks disrespectful and also against parental sayings becomes a phenomenon often encountered in society particularly in coastal communities. Family is very important in child education. The problem formula in this study is (1) How is the behaviour of children in the family? (2) What kind of factors affects the child's crisis of morality in the family? The purpose of the study is (1) to find out how child behaviour in the family is. (2) to find out what factors affect the child's crisis of morality in the family. To answer the question the researcher used a type of qualitative descriptive research in his research. In data collection techniques, researchers use interview and observation methods. Then, data analysis techniques are data reduction, data presentation and conclusion withdrawal